2018
DOI: 10.1016/j.rehab.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related low back pain in women in Turkey: Prevalence and risk factors

Abstract: This cross-sectional study is the largest study of PRLBP in the literature and showed that about 1 in 2 women have PRLBP in any stage of pregnancy. History of LBP related and unrelated to previous pregnancy and menstruation are strong risk factors for PRLBP. Receiving no housework assistance is another risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
45
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 29 publications
9
45
1
5
Order By: Relevance
“…[ 26 29 ] It has been reported that most pregnant women experienced LBP throughout the period of their pregnancy, delivery, and even after birth. [ 30 ] Of these, PPLBP was one type of LBP that occurred in pregnancy women after their delivery. [ 20 ] Several treatment options are utilized to treat this special condition.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 29 ] It has been reported that most pregnant women experienced LBP throughout the period of their pregnancy, delivery, and even after birth. [ 30 ] Of these, PPLBP was one type of LBP that occurred in pregnancy women after their delivery. [ 20 ] Several treatment options are utilized to treat this special condition.…”
Section: Discussionmentioning
confidence: 99%
“…By other studies that state that increased physical stress due to homework can be associated with risk factors for low back pain in pregnant women. (Sencan, Ozcan-Eksi, Cuce, Guzel, & Erdem, 2017) Supported by other studies also revealed that low back pain is most commonly experienced by housewives due to many activities in an unfavorable position, where lower back pain is one of the disorders of the musculoskeletal system caused by daily activities that ignore the problem of body position. (Shonafi, 2012) The decrease in intensity of low back pain in the intervention group was greater than in the control group marked by p-value 0.001 (<0.05).…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of pregnancy-related LBP and pelvic girdle pain PGP varied wildly between studies, with their prevalence ranging between 3.90% and 89.88% (Kovacs et al, 2012;Wu et al, 2004;Bastiaanssen et al, 2005). It has been demonstrated that about 45% of pregnant women and 25% of postpartum women (from birth till 6 to 8 weeks after birth (Leahy-Warren & McCarthy, 2011)) suffer from either lumbar pain or pelvic girdle pain (Larsen et al, 2013;Sencan et al, 2018). According to a previous study done on nurses from both genders in Jordan, the prevalence of LBP was 69%, 1-year prevalence was 78.9%, while the cumulative prevalence was 83.6%, most of them were females (70.3%) (Suliman, 2018).…”
Section: Discussionmentioning
confidence: 99%